Effect of maturity at harvest on yield, composition, and feeding value of forage and grain sorghum silages - Hamma, S.; Kirch, B.; Downey, B.; White, J.; Bolsen, K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In the last 2 years, three trials were conducted to determine the influence of hybrid and stage of maturity at harvest on silage yield, composition, and nutritive value for 15 forage and nine grain sorghum hybrids. Agronomic data, such as days to half bloom, plant height, and whole-plant dry matter (OM) and grain yields, were also obtained. In Trial 1, Pioneer 947, Acco Paymaster 351, and DeKalb 25E forage sorghum hybrids had different whole-plant OM and crude protein (CP) contents. Whole-plant OM increased, whereas CP generally decreased with advancing maturity. Hybrid affected both DM intake and CP digestibility. Results indicated that the late-dough stage of maturity optimized both yield and nutritive value. In Trials 2 and 3, grain sorghums reached the late-dough stage in fewer days than forage sorghums. The whole-plant DM and CP contents and grain yields differed considerably among the forage sorghums, and all were lower than values for the grain sorghum hybrids. However, Whole-plant DM yields were generally higher, but much more variable for the forage than for the grain sorghums. These results substantiate that large variations exist among forage sorghums and between grain and forage sorghum hybrids. Sorghums with higher DM and grain content should be favored and harvested at the late-dough stage for silage.
Keywords: Beef; Maturity; Yield; Composition; Feed value; Sorghum silage